(untitled) (Research, Society and Development, 2020)
The study explored the theory of multiple intelligences, more specifically the spatial one that has the capacity to form mental models (image), perceive the world, effect transformations or be able to recreate aspects of visual experience. In this context, strategies that use adapted comic books can be important didactic and metaphorical resources for teaching. The resource tends to enhance the teaching process by associating the situations presented in the stories with the students’ prior knowledge, with a view to meaningful learning. The research is characterized as qualitative with characteristics of a case study in which it sought to generate knowledge for the solution of the problem found by teachers of basic education in relation to learning. In this way, it starts from its contextualization for the elaboration of an activity that used a comic strip adapted from “Chico Bento at Shopping Geométrico” with the objective of relating the content with his images as a didactic resource for the re / construction of concepts of geometry. The study was carried out in a State Public School in the city of Santo Ângelo / RS in two high school classes. One, with 28 students with an average age of 24 years and the other, 24 students with an average age of 17 years. The research demonstrated, through its results, that comics facilitate learning and can be explored for any content or age, making the class more dynamic. Still, it made it possible for the objective to be achieved, as students developed the ability to read and understand mathematical concepts more easily.